Prevalence and molecular characterization of Cryptosporidium spp. in cattle in central and Western Inner Mongolia, China - Yan, Xinlei; Guo, Wenhui; Liang, Ru; Li, Ruifeng; Kang, Wenbin (Frontiers in Veterinary Science, 2025)
Cryptosporidium spp. are apicomplexan parasites that can cause diarrhea in humans and animals, posing a health risk to both animals and humans. Molecular epidemiological analysis provides essential data for understanding Cryptosporidium transmission, treatment, and control. In this study, SSU rRNA was used to determine the prevalence of Cryptosporidium in cattle. A total of 847 fecal samples were collected from 16 farms in central and western Inner Mongolia (Hohhot, Ordos, Bayan Nur and Baotou), and 15.94% (135/847) of samples were positive. Overall, Cryptosporidium was detected in all seasons. Calves up to 2 months of age were found with the highest rate of infection (33.33%). In older animals, there was a significant decline in infection rates with increasing age. The species, C. parvum (n = 105), C. andersoni (n = 21) and C. bovis (n = 9) were detected, individually, or in mixed infections involving two or three Cryptosporidium spp., and five subtypes of C. parvum (IIdA17G1, IIdA17G2, IIdA18G1, IIdA19G1, IIdA20G1) were identified. Our findings provide data to support the epidemiological control of Cryptosporidium infection in cattle.